THE Garlic (Allium sativum L.) – A Promising Anti-cancer Drug - Venkatesh, Sama; Aleem Ullah, Ayesha; Owaisuddin, Mohammed; Bolledu, Rajesh; Kiran, A Ravi (Asian Journal of Pharmaceutical Research and Development, 2021)
Globally cancer is the leading cause of death. The popular treatments in cancer therapies areradiation, surgery, chemo-therapy, involves high risk and expensive. The present day, modern cancer therapies are associated with several toxicities and lack of quality of life. Herbal remedies for cancer treatment are found notion to the Oncologists. Garlic known as Allium sativum (Family: Liliaceae), is one of the promising drug found to treat cancer patients and also to treat the toxicity effects produced by other cancer treatment. By consuming garlic regularly it shows protection to cancer and many ailments. Allicin is a major pharmacological component of garlic, reported to have anti-cancer properties and also used to treat drug-induced toxicity.